2001
DOI: 10.1002/1522-2683(200109)22:16<3401::aid-elps3401>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidation of low-density lipoprotein on drug binding affinity studied by high performance frontal analysis-capillary electrophoresis

Abstract: The effect of oxidation of low-density lipoprotein (LDL) on the enantioselective drug binding affinity was investigated using high performance frontal analysis--capillary electrophoresis (HPFA-CE). Verapamil and nilvadipine enantiomers were used as the chiral model drugs. LDL was oxidized with copper sulfate for 0, 0.5, 1, 2, and 12 h at 37 degrees C. The HPFA-CE method enabled microdetermination of unbound drug concentrations in native and oxidized LDL solutions. It was found that the bindings between LDL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The authors concluded that CE-FA is the method of choice, being less laborious than HD and VP methods, simple, robust, and applicable to multiple equilibria [15]. In addition to albumin binding, the FA method has been used to study the interaction of low molecular weight compounds with plasma lipoproteins [23,29,[38][39][40][41], a 1 -acid glycoprotein [23,25,[42][43][44], simulated cord blood serum [26,30], human plasma [31], serum protein mixtures and human serum [23].…”
Section: Introductionmentioning
confidence: 94%
“…The authors concluded that CE-FA is the method of choice, being less laborious than HD and VP methods, simple, robust, and applicable to multiple equilibria [15]. In addition to albumin binding, the FA method has been used to study the interaction of low molecular weight compounds with plasma lipoproteins [23,29,[38][39][40][41], a 1 -acid glycoprotein [23,25,[42][43][44], simulated cord blood serum [26,30], human plasma [31], serum protein mixtures and human serum [23].…”
Section: Introductionmentioning
confidence: 94%
“…Otherwise the free concentrations determined would be associated with an error. Experiments strongly indicate that low-molecular-weight ligand-HSA [34], drug-a 1 -acid glycoprotein (AGP) [48][49][50][51], and drug-lipoprotein [41] binding fulfil these requirements. The order of magnitude of the errors arising from not complying with the mobility restrictions has not been assessed.…”
Section: Requirements For Using Ce-famentioning
confidence: 99%
“…The binding of propranolol enantiomers to HDL and LDL was not enantioselective; the total binding affinity of propranolol to LDL (4.01610 5 M 21 ) was 18-fold of that of propranolol-HDL binding (2.38610 4 M 21 ) [102]. In a study on the effect of oxidation of LDL on enantioselective drug binding [103], the binding was not enantioselective at any oxidation stage. Similar results were obtained in studies of enantiomers of nilvadipine interacting with LDL and HDL [104].…”
Section: Protein-small Molecule Interactionmentioning
confidence: 99%